Challenges to theology - Oviedo, Lluis (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
The scientifically attested assumption that the human mind has a physicalsubstrate carries many consequences for the theological understanding of humanbeings and the fundamentals of religious experience. [...]